2013
DOI: 10.1038/cddis.2013.68
|View full text |Cite
|
Sign up to set email alerts
|

Nox4-dependent ROS modulation by amino endoperoxides to induce apoptosis in cancer cells

Abstract: Tumor metastasis is the main cause of death in cancer patients. Anoikis resistance is one critical malefactor of metastatic cancer cells to resist current clinical chemotherapeutic treatments. Although endoperoxide-containing compounds have long been suggested as anticancer drugs, few have been clinically employed due to their instability, complex synthesis procedure or low tumor cell selectivity. Herein, we describe a one-pot strategy to synthesize novel amino endoperoxides and their derivatives with good yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 41 publications
3
18
0
Order By: Relevance
“…Nox4, a member of the NOX family of NADPH oxidases, is responsible for the production of large amounts of ROS [20]. It was reported that Nox4-dependent ROS modulation can induce apoptosis in high Nox4-expressing cancer cells [18]. In our study, increased ROS was detected in PA-treated AML12 cells.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Nox4, a member of the NOX family of NADPH oxidases, is responsible for the production of large amounts of ROS [20]. It was reported that Nox4-dependent ROS modulation can induce apoptosis in high Nox4-expressing cancer cells [18]. In our study, increased ROS was detected in PA-treated AML12 cells.…”
Section: Discussionsupporting
confidence: 59%
“…Routinely, mitochondrial dysfunction, particularly the increased Nox4, leads to oxidative stress [18]. Here, the reactive oxygen species (ROS) level was investigated using DCF assay.…”
Section: Resultsmentioning
confidence: 99%
“…S7D). Three other NOX4 inhibiting compounds, imipramine blue, an aminoendoperoxide designated 4-Me (48,49), and GKT137831, an orally available dual NOX1/4 inhibitor (50), which became recently commercially available, likewise inhibited growth of FLT3ITD transformed cells in a dose-dependent manner ( Fig. S7E-H).…”
Section: Nox4 Is Important For Flt3itd-mediated Cell Transformation Imentioning
confidence: 88%
“…From the Venn Diagram shown in Fig.3, only “NOX4” [38] is selected in both DNA methylation and gene expression profiles. Note that, gene expression and DNA methylation may be correlated.…”
Section: Tests On Real Datamentioning
confidence: 99%